Policy Review On Returning Protected Area East Coast Of Surabaya - Herdinawati, Betty (Muhammadiyah University Press, 2020)
This study aims to identify steps to restore the function of the protected area of East Coast of Surabaya (Pamurbaya) by the government, to analyze the impact on the fulfillment of the rights of the people residing at Wisma Tirto Agung Phase IV, and to analyze the impact caused by evictions. This study used a qualitative analysis method with sociolegal research type, as well as an empirical juridical approach. The data used are primary data sourced from interviewers and other secondary data. This research was conducted on the basis of a violation of the sale and purchase of land plots which continued with the construction of residents' houses in the protected area of East Coast Surabaya (Pamurbaya), namely in Gunung Anyar District, Rungkut District, Sukolilo District and Mulyorejo District. The results of this study indicate that the Surabaya Municipal Government has not provided a clear solution to the cases that occurred so that the residents of Wisma Tirto Agung stage IV continue to live in their respective homes. The plan to return the function of the protected area by means of eviction is still in the assessment stage because the Surabaya City Government cannot decide to evict without paying attention to the rights of the community to have a proper place to live. In carrying out evictions, of course there are impacts that arise from psychological, economic, and social aspects.Â Keywords: Protected Area, Right to House, Eviction